Hydrogenated conjugated diene-arylethene random copolymer, preparation method and application in phase change material flexible clamp

Through the preparation of hydrogenated conjugated diene-arylethylene random copolymer, the limitations of existing phase change material fixtures in terms of use temperature, phase change temperature, fluidity and elastic modulus are solved, and efficient weak rigid machine processing is achieved, and the materials are friendly to human body and environment.

CN119708355AActive Publication Date: 2025-03-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311264290.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2025-03-28
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

Existing phase change material fixtures have limitations in terms of usage temperature, phase change temperature, fluidity and elastic modulus, and it is difficult to meet the needs of processing weak rigid parts.

Method used

Using hydrogenated conjugated diene-arylethylene random copolymer, materials with high flowability, moderate hardness and high elastic modulus are prepared through selective hydrogenation treatment and anion polymerization technology, and applied to phase change material flexible fixtures.

Benefits of technology

It achieves the ability to provide good flowability and elastic modulus at high operating temperatures to meet the needs of processing weak rigid parts. At the same time, the special structure of the material ensures its resistance under high-frequency impact and its friendliness to the human body and the environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708355A_ABST
    Figure CN119708355A_ABST
Patent Text Reader

Abstract

The invention discloses a hydrogenated conjugated diene-arylethene random copolymer, a preparation method thereof and application of the hydrogenated conjugated diene-arylethene random copolymer in a phase-change material flexible clamp. The hydrogenated conjugated diene-arylethene random copolymer is obtained by performing alkenyl selective hydrogenation on an arylethene-conjugated diene random copolymer; the hydrogenated conjugated diene-aryl ethylene random copolymer is fused and compounded with an oil product and / or a solid organic matter, has the advantages of higher hardness, higher elastic modulus, better high-frequency impact resistance, moderate melting temperature, low viscosity in a molten state, easiness in flowing and higher use temperature, does not adhere to or wind a cutter when being used in a solid state, is easy to remove from a workpiece, and can be applied to the field of cutting tools. The flexible clamp has the characteristics of being environment-friendly, friendly to human and environment and capable of being repeatedly used, and can be used as a main component of a phase change material flexible clamp in a weak-rigidity machine part machining process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a hydrogenated conjugated diene-aryl vinyl random copolymer, in particular to a hydrogenated conjugated diene-aryl vinyl random copolymer with high fluidity, high elastic modulus, good impact resistance, high operating temperature and suitable hardness, and also to a preparation method thereof, and application in preparing a flexible clamp for phase change materials, belonging to the technical field of lithium-based polymer materials. Background Art

[0002] With the development of industry, various thin-walled parts and large-sized weak rigid parts are constantly used in various fields such as aerospace, automobiles, etc., and they also face the problem of how to process them. In the processing of weak rigid parts, due to the relatively low rigidity of the workpiece and poor processing technology, under the influence of cutting force, cutting vibration, cutting heat and other factors, the milling process is prone to problems such as tool deflection, deformation, vibration, etc., and the processing quality is difficult to control. In severe cases, the workpiece will be scrapped. This situation is particularly prominent in the aerospace industry.

[0003] In order to solve the processing problem of weak rigid parts in industry, repeated finishing or deformation pre-compensation are often used. However, repeated finishing and deformation pre-compensation do not change the essential characteristics of low rigidity of weak rigid parts, and the processing efficiency is low. In this case, phase change material flexible fixtures show their unique advantages as a new solution.

[0004] Machine tools are basic tools for metal processing, and machine tool fixtures are basic components of metal processing equipment. They are the interface between workpieces and machine tools, cutting tools, robots and other equipment. Their flexibility has a vital impact on modern manufacturing technology.

[0005] Flexibility generally refers to variability or adaptability. The flexibility of a fixture refers to its ability to adapt to parts of different shapes and sizes. Flexible fixtures are a large family, including modular fixtures, programmable fixtures, general flexible fixtures, phase change material flexible fixtures and other fixtures. Phase change material flexible fixtures are referred to as phase change material fixtures, which are divided into two categories: true phase change material fixtures and pseudo phase change material fixtures.

[0006] The fixture based on phase change material has unique characteristics, with a large clamping area and uniform clamping force. It is especially suitable for clamping workpieces with low rigidity and complex shapes. Such workpieces are placed in the phase change material in the liquid phase and then the phase change material is quickly transformed into a solid state under certain external stimulation conditions (such as changes in temperature, magnetic field, and current) to achieve the purpose of uniformly clamping the workpiece. When the processing is completed, the phase change material is quickly changed from solid to liquid, so that the workpiece can be easily removed.

[0007] There are many phase change materials that can be used for machine tool fixtures. Using different phase change materials, various types of fixtures can be obtained, generally including the following categories: water-ice, wax-based materials, low melting point alloys (such as lead-tin-bismuth alloys), magnetorheological materials, and electrorheological materials; the above phase change materials each have their own application characteristics and also have their own limitations.

[0008] From the perspective of the use requirements of phase change material fixtures, phase change material fixtures need to be able to undergo solid-liquid phase change under certain conditions, have good fluidity in the liquid phase, have greater hardness and elastic modulus in the solid phase, not break under high-frequency impact, the material does not adhere to or entangle on the processing tool, is easy to remove from the workpiece, can be reused, be friendly to people and the environment, and have no odor.

[0009] p-Methylstyrene, formally known as 4-methylstyrene (p-Methylstyrene, PMS), is a homologue of styrene and has similar chemical properties to styrene. It can be obtained through various catalytic systems to form polymethylstyrene (PPMS). Compared with polystyrene, its biggest feature is good thermal performance. Highly crystalline PPMS has a higher glass transition temperature, Vicat softening point and heat deformation temperature. The glass transition temperature of heat-resistant PPMS is 113°C, which is 11% higher than that of polystyrene, the Vicat softening point is 6% higher, and the heat deformation temperature is 7% higher. Its hardness is higher than that of polystyrene, and its mechanical properties are slightly lower or basically equivalent.

[0010] α-Methylstyrene (English name: Alpha-Methylstyrene) is a colorless liquid with a pungent odor. It polymerizes when heated and is flammable. It can be used to produce coatings and plasticizers, and is also used as a solvent and organic synthesis. 4-tert-butylstyrene, also known as 4-tert-butylstyrene (English name: 1-tert-butyl-4-ethenylbenzene), is also a derivative of styrene. Like α-methylstyrene, 4-tert-butylstyrene and 4-methylstyrene, the thermal properties of the polymer are better than those of polystyrene. Also like 4-methylstyrene, when copolymerized with other monomers, the copolymer is the same as the copolymer of styrene and also shows the same characteristics as the monomer. Internationally, as early as the 1980s, industrial products of methylstyrene were supplied to the market. In recent years, a few manufacturers in my country have gradually begun to produce polymerization-grade industrial products. For example, the random copolymer of butadiene-4-methylstyrene obtained by an anionic catalytic system has a structure similar to that of solution-polymerized styrene-butadiene rubber. Its physical structure, properties, processing properties and product performance are close to those of solution polymerized styrene butadiene rubber. Some properties, such as wear resistance and heat resistance, are better than those of solution polymerized styrene butadiene rubber. It can be used as a substitute for solution polymerized styrene butadiene rubber.

[0011] In a lithium anion catalyst system, p-methylstyrene can replace styrene to synthesize a random copolymer of butadiene and p-methylstyrene. The melting point of the obtained butadiene-p-methylstyrene random copolymer is higher than that of butadiene-styrene random copolymer, that is, solution-polymerized styrene-butadiene rubber. Butadiene and methylstyrene can also be copolymerized in a block manner, and the content of methylstyrene in the block manner can be higher, but the viscosity of the molten state will also be greater, which is contrary to the requirements for phase change material fixtures.

[0012] α-Methylstyrene and p-tert-butylstyrene are the same as p-methylstyrene.

[0013] Isoprene, IUPAC nomenclature is 2-methyl-1,3-butadiene, is an organic compound with the chemical formula C5H8. It is a colorless volatile liquid, insoluble in water, soluble in most organic solvents such as ethanol and ether. It is mainly used in the production of polyisoprene rubber and is also the second monomer of butyl rubber. It is also used in the manufacture of pesticides, medicines, fragrances and adhesives. Isopentadiene, IUPAC nomenclature is 1,3-pentadiene, with the chemical formula C5H8. It has two isomers, cis and trans, and is mainly used in the production of petroleum resins. Isoprene, isoprene and butadiene are all conjugated diene hydrocarbons, which can be randomly copolymerized with aromatic vinyl in lithium-based anionic polymerization to form random copolymers.

[0014] At present, there is no report on the successful application of hydrogenated conjugated diene-aryl vinyl random copolymer as a phase change material fixture. Summary of the invention

[0015] In view of the problems that the existing phase change material fixtures have limited operating temperature, the phase change temperature is too high or too low, the fluidity in the liquid phase is poor, and the elastic modulus in the solid phase is not large, the first object of the present invention is to provide a hydrogenated conjugated diene-aryl vinyl random copolymer having excellent properties such as high fluidity, moderate hardness, high elastic modulus, and high operating temperature.

[0016] The second object of the present invention is to provide a method for preparing the hydrogenated conjugated diene-aryl vinyl random copolymer with simple operation, low cost and mild conditions.

[0017] The third purpose of the present invention is to provide an application of a hydrogenated conjugated diene-aromatic vinyl random copolymer, which has the characteristics of good melt fluidity, high elastic modulus, high hardness, and high operating temperature. It is used to prepare a phase change material flexible clamp. Its comprehensive performance meets the requirements of the phase change material flexible clamp in the weak rigidity machine part processing technology. It has a moderate phase change temperature, good liquid phase fluidity, large solid phase elastic modulus, high operating temperature, does not adhere to or entangle on the processing tool, is easy to peel off and remove from the machine part, is friendly to people and the environment, and can be reused.

[0018] In order to achieve the above technical objectives, the present invention provides a hydrogenated conjugated diene-aryl vinyl random copolymer, which is obtained by selectively hydrogenating the alkenyl group of the conjugated diene-aryl vinyl random copolymer; the mass percentage composition of the aryl vinyl unit and the conjugated diene unit in the conjugated diene-aryl vinyl random copolymer is 20-65%:35-80%; the quantity ratio of the 1,4-structural unit to the 1,2-structural unit and / or the 3,4-structural unit of the conjugated diene unit in the conjugated diene-aryl vinyl random copolymer is 0.3-2:1.

[0019] The hydrogenated conjugated diene-aryl vinyl random copolymer provided by the present invention has a special molecular structure. The conjugated diene unit and the aryl vinyl unit in the butadiene-p-methylstyrene random copolymer present a random copolymerization structure, and contain an appropriate proportion of aryl vinyl units and 1,2-structural units and / or 3,4-structural units of butadiene conjugated diene hydrocarbons. After selective hydrogenation of the alkenyl group, various side groups on the main chain are converted into ethyl, propenyl, and isopropyl side chains, and the side chains also contain rigid p-methylbenzene rings, α-methyl, and p-tert-butylbenzene rings. This special molecular structure gives the hydrogenated conjugated diene-aryl vinyl random copolymer good tensile properties, hardness, elastic modulus and melt fluidity, and a high melting temperature, which can better meet the performance requirements of the flexible fixture of the phase change material.

[0020] The mass ratio of the aryl vinyl unit to the conjugated diene unit in the conjugated diene-aryl vinyl random copolymer provided by the present invention is an important factor affecting the hardness of the hydrogenated conjugated diene-aryl vinyl random copolymer, and is also a factor affecting the melt fluidity. The aryl vinyl content is positively correlated with the hardness, and a high aryl vinyl content has an adverse effect on the melt fluidity. As a preferred embodiment, the proportion of the aryl vinyl in the total mass is 20-65%.

[0021] As a preferred solution, the number average molecular weight of the conjugated diene-aryl vinyl random copolymer is 45,000 to 100,000, and the molecular weight distribution index is ≤1.08. The molecular weight has an influence on the tensile properties, hardness, melt fluidity, etc. of the hydrogenated conjugated diene-aryl vinyl random copolymer. The molecular weight is positively correlated to the tensile properties and the molecular weight is positively correlated to the hardness, but a large molecular weight is not favorable for the melt fluidity. Considering the existing production process of solution-polymerized styrene-butadiene rubber, the molecular weight is selected between 45,000 and 100,000, and the molecular weight distribution index is ≤1.08.

[0022] As a preferred solution, the hydrogenation degree of the alkenyl group in the hydrogenated conjugated diene-aryl vinyl random copolymer is not less than 98%, and the hydrogenation degree of the benzene ring is not more than 5%. After the selective hydrogenation of the alkenyl group, rigid p-methyl, α-methyl, p-tert-butyl and other groups are retained, and a large number of short branched chains and flexible alkane chains are generated.

[0023] The hydrogenated conjugated diene-aryl vinyl random copolymer provided by the present invention has the following chemical structural formula (specifically described using butadiene-p-methylstyrene as an example):

[0024]

[0025] Here, x, y, and z are all degrees of polymerization, x is the number of hydrogenated butadiene units with a 1,4-structure, y is the number of hydrogenated butadiene units with a 1,2-structure, and z is the number of p-methylstyrene units.

[0026] From the perspective of molecular structure, the melt viscosity and molecular weight of hydrogenated aromatic vinyl thermoplastic elastomer with block structure have the following relationship: η=KM 5.5 , where η is the viscosity, K is a constant, and M is the molecular weight; for homopolymers and random copolymers, η = KM 3.4 , the symbolic meaning is the same as the above formula. Obviously, the block structure is not conducive to the low viscosity required by the target material. The polyaryl vinyl block in the hydrogenated aryl vinyl thermoplastic elastomer also provides good hardness, but on the one hand, the material hardness can also be improved by random copolymerization of aryl vinyl and conjugated diene, and secondly, the hardness can also be improved by adjusting the formula of the phase change material flexible fixture, and the cost is even lower. At the same time, the hydrogenated conjugated diene-aryl vinyl random copolymer of the present invention, its random copolymerization process is also simpler than the synthesis process of the block structure, and has more advantages.

[0027] The hydrogenated conjugated diene-aryl vinyl random copolymer used in the present invention has better melt fluidity compared with the hydrogenated conjugated diene-aryl vinyl block copolymer.

[0028] In the conjugated diene-aryl vinyl random copolymer of the present invention, the aryl vinyl unit and the conjugated diene unit are relatively evenly distributed according to the molar ratio of the two. Although the aryl vinyl unit and the conjugated diene unit are relatively evenly distributed, the degree of randomization cannot reach 100% in practice, so that a part of the microblock of polyaryl vinyl exists in the chain segment, and the microblock can improve the hardness of the material, but also increases the viscosity of the material in the molten state, and the microblock is large and may form a thermoplastic elastomer, so the microblock must be controlled within a suitable range. The control of the microblock is closely related to the structure regulator, the polymerization temperature and the feeding method. The polymerization temperature has a very important influence on many aspects, and is basically controlled at 60-80°C in industrial production, and the feeding method is also affected by factors such as cost and control in the production process, and is also basically fixed. Therefore, the present invention controls the microblock by the variety and concentration of the structure regulator.

[0029] The 1,4-structure of butadiene forms polyethylene after hydrogenation, and the 1,2-structure forms poly-1-butene after hydrogenation. The 1,4-structure of isoprene forms a polyethylene unit and a polypropylene unit connected together after hydrogenation. The 1,2-structure is hydrogenated to obtain poly-2-methyl-1-butene, and the 3,4-structure is hydrogenated to obtain poly-3-methyl-1-butene. The 1,4-structure of isoprene is hydrogenated to obtain a polyethylene unit and a polypropylene unit connected together, the 1,2-structure is hydrogenated to obtain poly-1-pentene, and the 3,4-structure is hydrogenated to obtain poly-2-pentene. Except for the 1,4-structure of butadiene, the other structures have side groups, so they can all destroy the crystallization of the main chain and exhibit rubber properties in terms of macroscopic properties.

[0030] If there are more than five consecutive polyethylene units, it is easy to crystallize, which is manifested as polyethylene plastic segments on a macro scale. If there are too many butadiene 1,4-structures in the copolymer, the glass transition temperature will rise and the rubber properties of the material will disappear. Therefore, in the molecular design stage, the side groups formed by the aromatic vinyl units and 1,2-structures or 3,4-structures after hydrogenation can destroy the crystallization caused by the excessive length of polyethylene units under the condition of reaching a certain proportion and relatively uniform distribution in the chain segment, so that the material can maintain a balance between tensile properties and hardness.

[0031] In summary, the present invention obtains a hydrogenated conjugated diene-aryl vinyl random copolymer that meets the performance requirements through the unique structure of the hydrogenated conjugated diene-aryl vinyl random copolymer, specifically, the molecular weight, the mass ratio of aryl vinyl to conjugated diene, the content of polyaryl vinyl microblocks, the uniformity of distribution of aryl vinyl units and conjugated diene units in the chain segments, the total amount of 1,2-structures and 3,4-structures in the conjugated diene units and the ratio and uniformity of distribution of the 1,4-structure, and the selective hydrogenation to eliminate the double bonds in the conjugated diene units in the chain segments.

[0032] As a preferred solution, the degree of hydrogenation of the alkenyl group in the conjugated diene-aryl vinyl random copolymer is ≥98%, and the degree of hydrogenation of the benzene ring is ≤5%. The high degree of selective hydrogenation of the alkenyl group can give the polymer good flexibility, good processing performance, good heat resistance and aging resistance, and can be reused. If the alkenyl group is not hydrogenated or the degree of hydrogenation is very low, although it can also be used as the main material of the phase change material flexible fixture, the resulting product has a short storage time and is prone to aging during use, which is not conducive to the reuse of the material.

[0033] As a preferred solution, the aromatic vinyl unit is at least one of p-methylstyrene, α-methylstyrene, and p-tert-butylstyrene; the conjugated diene unit is at least one of isoprene, isoprene, and butadiene. A combination of at least one styrene derivative such as p-methylstyrene, α-methylstyrene, and p-tert-butylstyrene and at least one of isoprene, isoprene, and butadiene in conjugated diene hydrocarbons can be anion polymerized to obtain a random copolymer similar to solution-polymerized styrene-butadiene rubber. Combinations of various styrene derivatives and conjugated diene hydrocarbons, the structures obtained by anion polymerization are similar to the random copolymers of the present invention, and can also be applied to phase change material flexible clamps.

[0034] The present invention also provides a method for preparing a hydrogenated conjugated diene-aryl vinyl random copolymer, which comprises the following steps: adding aryl vinyl and conjugated diene mixed monomers to an anionic polymerization system for random copolymerization to obtain a conjugated diene-aryl vinyl random copolymer gum solution, and subjecting the conjugated diene-aryl vinyl random copolymer gum solution to a selective hydrogenation reaction to obtain the product.

[0035] As a preferred solution, the conjugated diene monomer and the aromatic vinyl monomer are uniformly mixed and then added into the anionic polymerization system for polymerization. The highly uniformly mixed conjugated diene monomer and aromatic vinyl monomer participating in the copolymerization reaction is beneficial to improving the degree of random copolymerization.

[0036] As a preferred solution, the conjugated diene monomer and the aromatic vinyl monomer are mixed by the following method: 1) the inside of a sealed tank I is evacuated to a negative pressure, and the aromatic vinyl monomer is injected into the sealed tank I; 2) the inside of a sealed tank II is evacuated to a negative pressure, and the conjugated diene monomer is injected into the sealed tank II; 3) the aromatic vinyl monomer in the sealed tank I is pressed into the sealed tank II by nitrogen, and the nitrogen pressure in the sealed tank II is used to fully mix the aromatic vinyl monomer and the conjugated diene monomer, or the conjugated diene monomer in the sealed tank II is pressed into the sealed tank I by nitrogen, and the nitrogen pressure in the sealed tank I is used to fully mix the conjugated diene monomer and the aromatic vinyl monomer.

[0037] As a preferred solution, the nitrogen pressure of the sealed tank I or sealed tank II is maintained at 0.4-0.6 MPa.

[0038] As a preferred solution, the conjugated diene and aromatic vinyl mixed monomers are added all at once, in batches, or slowly and continuously. In order to increase the degree of random copolymerization, it is best to use a continuous and slow addition method.

[0039] As a preferred solution, the anionic polymerization system comprises a non-polar alkane solvent, an initiator and a structure regulator.

[0040] As a preferred solution, the non-polar alkane solvent is cyclohexane; the amount of cyclohexane used maintains the total mass percentage concentration of polymerized monomers in the anionic polymer system within a range of 5 to 15%.

[0041] As a preferred solution, the initiator is n-butyl lithium, and other common alkyl lithium or aryl lithium are also common initiators in the art.

[0042] As a preferred solution, the structure regulator is at least one of tetrahydrofurfuryl propane, tetramethylethylenediamine, tetrahydrofurfuryl alcohol ethyl ether, and tetrahydrofuran. As a preferred solution, the amount of the structure regulator relative to the non-polar alkane solvent is 70 to 290 mg / kg. The present invention comprehensively controls the microblock content, the ratio of 1,2-structure, 3,4-structure and 1,4 structure by selecting an appropriate structure regulator and its concentration in the anionic polymerization system, while ensuring the content of 1,2-structure and 3,4-structure, the content of the microblock is also controlled, and a material that meets the required performance can be obtained.

[0043] The ratio of the total amount of 1,2-structure and 3,4-structure to the amount of 1,4-structure in the conjugated diene unit: The structure regulator added in the polymerization process of the present invention actually has three functions: first, it acts as a dissociating agent to dissociate the association of n-butyl lithium in a non-polar solvent, which is beneficial to improving the utilization efficiency of n-butyl lithium; second, it acts as a polymerization rate regulator to regulate the polymerization rate of aromatic vinyl and conjugated diene, thereby regulating the uniformity of the distribution of aromatic vinyl and conjugated diene in the polymer chain segment. The greater the regulating effect, the more uniform the distribution and the fewer microblocks; third, it acts as a structure regulator of conjugated diene to regulate the ratio of the total amount of 1,2-structure and 3,4-structure to 1,4-structure. The greater the regulating effect, the higher the total content of 1,2-structure and 3,4-structure. The latter two have opposite regulating directions, that is, the higher the content of 1,2-structure, the lower the content of microblock. Therefore, it is necessary to select the appropriate type and concentration of structure regulator.

[0044] As a preferred solution, during the random copolymerization process, the pressure is maintained in the range of 0.1 MPa to 0.5 MPa, the temperature is 60 to 80° C., and the time is ≥70 min (until the reaction is complete).

[0045] As a preferred solution, the conditions of the hydrogenation reaction are: hydrogen pressure of 1.0-2.0 MPa, hydrogenation reaction temperature of 70-75° C., and time of 1.5-2.5 h.

[0046] As a preferred solution, a combined hydrogenation catalyst of dicyclopentadiene titanium dichloride / dimethyl phthalate is used in the hydrogenation reaction. The preferred hydrogenation catalyst has a high selective hydrogenation effect on alkenyl.

[0047] In the hydrogenation reaction process of the present invention, the rubber is pressed into a hydrogenation kettle replaced by nitrogen, the temperature is raised to 70-75° C., a co-catalyst dimethyl phthalate is first added for passivation reaction for 5-15 minutes, and then a main catalyst dicyclopentadiene titanium dichloride is added, and a hydrogenation reaction is carried out under a hydrogen pressure of 1.0-2.0 MPa. The hydrogenation reaction is carried out for 1.5-2.5 hours, and the hydrogenation degree of the alkenyl group in the polymer is ≥98%, and the hydrogenation degree of the benzene ring is ≤5%.

[0048] The hydrogenated conjugated diene-aryl vinyl random copolymer prepared by the present invention needs to remove metal ions. The main process is: firstly, a small amount of soft water is used to terminate the reaction of hydrogenated glue for 15 minutes, then acidified with tert-butyl ester or citric acid for 30 minutes, and finally soft water with a volume ratio of 10% of the glue volume is added, emulsified for 15 minutes, centrifuged and allowed to stand, and the water phase is separated, and the process is repeated twice, and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionic acid n-octadecyl alcohol ester (1076) or a mixture thereof with tris[2,4-di-tert-butylphenyl] phosphite (168) is added to the remaining glue as an antioxidant. The glue is heated in water by steam, and after removing the solvent, it is placed in a blast drying oven at 60°C and dried for 8 hours to obtain the obtained glue.

[0049] The present invention also provides an application of a hydrogenated conjugated diene-aryl vinyl random copolymer, which is used for preparing a phase change material flexible fixture.

[0050] As a preferred solution, the hydrogenated conjugated diene-aryl vinyl random copolymer is melt-compounded with oil products and / or solid organic matter.

[0051] As a preferred solution, the mass percentage composition of the hydrogenated conjugated diene-aryl vinyl random copolymer and the oil product and / or solid organic matter is 20-40%:60-80%.

[0052] As a preferred solution, the oil product includes saturated liquid hydrocarbons; and the solid organic matter includes saturated solid hydrocarbons or saturated fats.

[0053] The technical solution of the present invention is to mix the hydrogenated conjugated diene-aryl vinyl random copolymer with oil and / or solid organic matter, melt it into a liquid, stir it evenly, and then cool and solidify it to obtain a mixed material. The mixed material can be used as a phase change material flexible fixture for the processing technology of weak rigid parts.

[0054] The main component of the solid organic matter in the technical solution of the present invention is a saturated organic matter, for example, it can be a hydrocarbon solid mixture mainly composed of straight-chain alkanes, preferably No. 58 paraffin, or a low-melting-point solid organic matter containing other elements, such as polyethylene wax, stearic acid, etc., preferably polyethylene wax. The main component of the oil product is a liquid hydrocarbon mixture mainly composed of straight-chain alkanes, preferably cosmetic grade No. 26 white oil, or a cycloalkane oil whose main component is saturated cycloalkane, and the preferred solution is KN4003.

[0055] The technical solution of the present invention preferably comprises cosmetic grade No. 26 white oil and No. 58 paraffin in the following mass percentages: 20-50% of hydrogenated butadiene styrene random copolymer, 20-60% of No. 58 paraffin and 20-50% of cosmetic grade No. 26 white oil, and mixes them together according to the above proportions, heats the mixture until it melts (temperature is 150-210° C.), stirs the mixture evenly while heating, and cools it naturally to a solid state to obtain the desired material.

[0056] The hydrogenated conjugated diene-aryl vinyl random copolymer provided by the technical solution of the present invention can be evenly melt-mixed with other conventional materials to prepare a phase change material flexible fixture, which is used in the processing technology of weak rigid parts. Compared with existing paraffin, low melting point metal, urea, water-ice and other materials, it has good fluidity in liquid state, large elastic modulus in solid state, good high-frequency impact resistance, high operating temperature, no entanglement, no adhesion to tools and workpieces, easy removal, no odor, harmless to the human body, environmentally friendly, and reusable.

[0057] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0058] 1. The hydrogenated conjugated diene-aryl vinyl random copolymer provided by the present invention has a special molecular structure, which is a hydrogenated aryl vinyl and conjugated diene random copolymer segment, rather than an aryl vinyl block copolymer structure, and the conjugated diene unit contains a suitable proportion of 1,2-structure and or 3,4-structure, and the conjugated diene unit is highly hydrogenated. This special molecular structure gives the polymer good comprehensive mechanical properties, especially high fluidity in the molten state, certain hardness and elastic modulus in the elastic state, and is very suitable as a phase change material flexible fixture after melt blending with other materials, and is used for the processing of weak rigid parts. It has the advantages of good fluidity in liquid state, high hardness and elastic modulus in solid state, good impact resistance, non-adhesion, winding processing tool, suitable solid-liquid phase change range, harmless to the human body, environmentally friendly, reusable, etc.

[0059] 2. The hydrogenated conjugated diene-aryl vinyl random copolymer of the present invention has four outstanding advantages: first, the special structure of the random copolymerization segment of aryl vinyl and conjugated diene, the random copolymerization of aryl vinyl and conjugated diene ensures that the elastomeric characteristics can be maintained when the mass percentage of aryl vinyl in the copolymer exceeds 50%, and the absence of polyaryl vinyl blocks makes the material have better fluidity in the molten state, and the molecular weight is controlled within a certain range, which ensures that the hydrogenated conjugated diene-aryl vinyl random copolymer has better fluidity in the molten state under the premise of maintaining a certain hardness and tensile properties; second, during the polymerization, the type and concentration of the polyaryl vinyl in the chain segment are controlled at the same time. The first is to selectively hydrogenate the conjugated diene-aryl vinyl random copolymer, and the second is to selectively eliminate the olefinic unsaturated bonds, thereby reducing the factors affecting the material properties and greatly improving the material's heat resistance, making it reusable and reducing costs. The third is to remove ions, thereby expanding the material's applicability to weak rigid parts of different materials, which is particularly evident in the aerospace field.

[0060] The preparation method of the hydrogenated conjugated diene-aryl vinyl random copolymer of the present invention is simple, low in cost and mild in process conditions, and meets the requirements of industrial production application. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 is the GPC of the random copolymer (styrene-butadiene) without hydrogenation.

[0062] Figure 2 This is the NMR image of the random copolymer (p-methylstyrene-isopentadiene). DETAILED DESCRIPTION

[0063] In order to further illustrate the details of the present invention, several embodiments are listed. The following embodiments are intended to illustrate the contents of the present invention, rather than to limit the scope of protection of the claims of the present invention.

[0064] Analysis method: Molecular weight and molecular weight distribution are determined by gel permeation chromatography; melt index test is carried out according to GB / T 3682-20008; hardness is in accordance with GB / T 2411-2008; 1,2 structure, 3,4 structure and 1,4 structure content are determined according to HNMR analysis results.

[0065] In the following examples, butadiene monomer and p-methylstyrene monomer are uniformly mixed by the following method: 1) negative pressure is evacuated inside sealed tank I, and p-methylstyrene monomer is injected into the sealed tank I; 2) negative pressure is evacuated inside sealed tank II, and butadiene monomer is injected into the sealed tank II; 3) the p-methylstyrene monomer in sealed tank I is pressed into the sealed tank II by nitrogen, and the p-methylstyrene monomer and butadiene monomer are fully and uniformly mixed by the nitrogen pressure (about 0.5 MPa) in sealed tank II.

[0066] Example 1

[0067] The preparation method is to prepare a base rubber with a number average molecular weight of 90,000, 40% p-methylstyrene and 60% butadiene, and then hydrogenate it.

[0068] 3000 ml of pure cyclohexane (water value < 20ppm) and 2.5 ml of ditetrahydrofurfuryl propane (prepared into 0.5 mol / L cyclohexane solution, the amount is equivalent to 100 mg / kg solvent) were added to a 5-liter polymerization kettle replaced with high-purity nitrogen, stirring was turned on, the temperature was raised to 60°C, 4.45 mmol of n-butyl lithium was added, and then a mixed monomer of 240 g of butadiene and 160 g of p-methylstyrene was added in five times on average, and the reaction temperature was controlled at 70°C. After the polymerization reaction was completed, the glue was introduced into a 5L hydrogenation kettle, the temperature was raised to 70°C, 5.0 mmol of n-butyl lithium was added, and the reaction was terminated with hydrogen for 10 minutes. 14 mmol of cocatalyst dibutyl phthalate and 0.5 g of main catalyst dicyclopentadiene titanium dichloride were added, the hydrogenation pressure was controlled at 1.2 MPa, and the hydrogenation reaction was carried out for two hours, and the cocatalyst was added twice in the middle, each time in an amount of 2 mL. After the hydrogenation reaction is completed, the hydrogenated gelatin is transferred to a water washing kettle, heated to 65°C, and the hydrogenated gelatin is terminated with 10 mL of soft water for 15 minutes, then acidified with 3.5 mL of tert-butyl decanoic acid (dissolved in 200 mL of cyclohexane) for 30 minutes, and finally emulsified and extracted with 350 mL of soft water for 15 minutes, centrifuged and allowed to stand, and the aqueous phase is separated, and this is repeated twice. The remaining gelatin is condensed by water vapor and dried to obtain a hydrogenated butadiene-p-methylstyrene random copolymer.

[0069] The performance test results are as follows:

[0070] The results of GPC analysis showed that the number average molecular weight of the base rubber was 89,000 and the molecular weight distribution was 1.04.

[0071] Iodine value analysis results: hydrogenation degree is 97.9%;

[0072] Due to performance requirements, the elastomer properties are not required to have strong tensile properties, and only the melt index and hardness are measured. The Shore A hardness is 83 and the melt index is 16.2g / 10min.

[0073] According to the mass ratio of 30% of the prepared hydrogenated butadiene-p-methylstyrene random copolymer, 35% of No. 58 paraffin, and 35% of No. 26 white oil, the mixture is mixed, heated to melt, mixed evenly, and then naturally cooled and solidified to room temperature. The Shore A hardness is 89, and it does not adhere to the tool when used in the phase change material flexible fixture.

[0074] High temperature aging test method: heat to liquid state, then naturally cool to solid state at room temperature, repeat 10 times, the product is still white and not yellow. The results are summarized in Table 1.

[0075] Example 2

[0076] A random copolymer base rubber with a number average molecular weight of 45,000, a p-methylstyrene content of 60%, and a butadiene content of 40% was prepared and then hydrogenated.

[0077] The preparation process is the same as that of Example 1. The formula for preparing the phase change material flexible clamp is 45% by mass of hydrogenated butadiene-p-methylstyrene random copolymer, 35% of No. 58 paraffin, and 20% of No. 26 white oil. The experimental results are shown in Table 1.

[0078] Example 3

[0079] A random copolymer base rubber with a number average molecular weight of 65,000, a p-methylstyrene content of 30%, and a butadiene content of 70% was prepared and then hydrogenated.

[0080] The preparation process is the same as in Example 1. The formula for preparing the phase change material flexible fixture is 30% by mass of hydrogenated butadiene-p-methylstyrene random copolymer, 40% of No. 58 paraffin, and 30% of No. 26 white oil. The experimental results are shown in Table 1:

[0081] Comparative Example 1

[0082] A random copolymer base rubber with a number average molecular weight of 90,000, a p-methylstyrene content of 40%, and a butadiene content of 60% was prepared without hydrogenation.

[0083] The preparation process is the same as that of Example 1. The formula for preparing the phase change material flexible clamp is 30% of unhydrogenated butadiene-p-methylstyrene random copolymer, 35% of No. 58 paraffin, and 35% of No. 26 white oil. The experimental results are shown in Table 1.

[0084] Heat to liquid state, then naturally cool to solid state at room temperature, repeat this process 10 times. The product turns yellow and cannot be used anymore, indicating serious aging.

[0085] Comparative Example 2

[0086] A random copolymer base rubber with a number average molecular weight of 65,000, a p-methylstyrene content of 10%, and a butadiene content of 90% was prepared and then hydrogenated.

[0087] The preparation process is the same as that of Example 1, but the 1,2-structure is controlled to be below 15%. The obtained glue solution is hydrogenated to obtain a plastic-like material, and a phase-change flexible clamp cannot be prepared.

[0088] The ratio of 1,2-structure of p-methylstyrene and butadiene affects the crystallinity of the polymer. If the p-methylstyrene content is too low and the ratio of 1,2-structure of butadiene is too low, the polymer crystallinity will be too high and lose elasticity.

[0089] Table 1: Application of various copolymers and phase change materials flexible clamps with different structures

[0090]

[0091]

Claims

1. A hydrogenated conjugated diene-aryl vinyl random copolymer, characterized in that: It is obtained by selective hydrogenation of the olefin group of a conjugated diene-aryl vinyl random copolymer; The mass percentage of the aryl vinyl unit and the conjugated diene unit in the conjugated diene-aryl vinyl random copolymer is 20-65%:35-80%; The quantitative ratio of 1,4-structural units to 1,2-structural units and / or 3,4-structures of the conjugated diene units in the conjugated diene-aryl vinyl random copolymer is 0.3 to 2:

1.

2. The hydrogenated conjugated diene-aryl vinyl random copolymer according to claim 1, characterized in that: The number average molecular weight of the conjugated diene-aryl vinyl random copolymer is 45,000 to 100,000, and the molecular weight distribution index is ≤1.

08.

3. A hydrogenated conjugated diene-aryl vinyl random copolymer according to claim 1 or 2, characterized in that: The hydrogenation degree of the alkenyl group in the conjugated diene-aryl vinyl random copolymer is not less than 98%, and the hydrogenation degree of the benzene ring is not more than 5%.

4. A hydrogenated conjugated diene-aryl vinyl random copolymer according to claim 1 or 2, characterized in that: The aromatic vinyl unit is at least one of p-methylstyrene, α-methylstyrene, and p-tert-butylstyrene; the conjugated diene unit is at least one of isoprene, isoprene, and butadiene.

5. The method for preparing a hydrogenated conjugated diene-aryl vinyl random copolymer according to any one of claims 1 to 4, characterized in that: In an anionic polymerization system, aromatic vinyl and conjugated diene mixed monomers are added for random copolymerization to obtain a conjugated diene-aromatic vinyl random copolymer gum, and the conjugated diene-aromatic vinyl copolymer gum is subjected to hydrogenation reaction to obtain the product.

6. The method for preparing a hydrogenated conjugated diene-aryl vinyl random copolymer according to claim 5, characterized in that: The p-methylstyrene and butadiene mixed monomers are obtained by mixing in the following method: 1) vacuuming the inside of a sealed tank I and injecting an aromatic vinyl monomer into the sealed tank I; 2) vacuuming the inside of a sealed tank II and injecting a conjugated diene monomer into the sealed tank II; 3) pressing the aromatic vinyl monomer in the sealed tank I into the sealed tank II with nitrogen, and fully mixing the aromatic vinyl monomer and the conjugated diene monomer with the nitrogen pressure in the sealed tank II; or, pressing the conjugated diene monomer in the sealed tank II into the sealed tank I with nitrogen, and fully mixing the conjugated diene monomer and the aromatic vinyl monomer with the nitrogen pressure in the sealed tank I.

7. The method for preparing a hydrogenated conjugated diene-aryl vinyl random copolymer according to claim 6, characterized in that: The nitrogen pressure of the sealed tank I or the sealed tank II is maintained at 0.4-0.6 MPa.

8. The method for preparing a hydrogenated conjugated diene-aryl vinyl random copolymer according to any one of claims 5 to 7, characterized in that: The aromatic vinyl and conjugated diene mixed monomers are added in a manner of all-at-once, batchwise or slowly and continuously.

9. The method for preparing a hydrogenated conjugated diene-aryl vinyl random copolymer according to claim 5, characterized in that: The anionic polymerization system comprises a non-polar alkane solvent, an initiator and a structure regulator.

10. The method for preparing a hydrogenated conjugated diene-aryl vinyl random copolymer according to claim 9, characterized in that: The non-polar alkane solvent is cyclohexane; The amount of cyclohexane used is to maintain the total mass percentage concentration of the polymerized monomers in the anionic polymer system within the range of 5 to 15%; The initiator is n-butyl lithium; The structure regulator is at least one of ditetrahydrofurfuryl propane, tetramethylethylenediamine, tetrahydrofurfuryl alcohol ethyl ether and tetrahydrofuran; The amount of the structure regulator relative to the non-polar alkane solvent is 70-290 mg / kg.

11. The method for preparing a hydrogenated conjugated diene-aryl vinyl random copolymer according to claim 5, characterized in that: During the random copolymerization, the polymerization pressure is maintained in the range of 0.1 MPa to 0.5 MPa, the temperature is 60 to 80° C., and the time is ≥70 min.

12. The method for preparing a hydrogenated conjugated diene-aryl vinyl random copolymer according to claim 5, characterized in that: The conditions of the hydrogenation reaction are: hydrogen pressure of 1.0-2.0 MPa, temperature of 70-85° C., and time of 1.5-2.5 h.

13. The method for preparing a hydrogenated conjugated diene-aryl vinyl random copolymer according to claim 5 or 12, characterized in that: In the hydrogenation reaction process, a combined hydrogenation catalyst of dicyclopentadiene titanium dichloride / dimethyl phthalate is used.

14. The use of a hydrogenated conjugated diene-aryl vinyl random copolymer according to any one of claims 1 to 4, characterized in that: Used to prepare flexible fixtures of phase change materials.

15. The use of a hydrogenated conjugated diene-aryl vinyl random copolymer according to claim 14, characterized in that: The hydrogenated conjugated diene-aryl vinyl random copolymer is melt-mixed with oil products and / or solid organic matter.

16. The use of a hydrogenated conjugated diene-aryl vinyl random copolymer according to claim 15, characterized in that: The mass percentage composition of the hydrogenated conjugated diene-aryl vinyl random copolymer and the oil product and / or solid organic matter is 20-50%:50-80%.

17. The use of a hydrogenated conjugated diene-aryl vinyl random copolymer according to claim 16, characterized in that: The oil products include saturated liquid hydrocarbons; the solid organic matter includes saturated solid hydrocarbons or saturated fats.

Citation Information

Patent Citations

  • Partially hydrogenated polystyrene-b-random copolymer conjugated diene / styrene copolymer and its preparation method and use

    CN106317350A

  • Sulfate-based styrene / hydrogenated conjugated diene / styrene block copolymer ionomer composite phase change material and preparation method thereof

    CN109777362A

  • Conjugated diene and monovinylarene random copolymer, and preparation method thereof

    CN110357998A

  • Hydrogenated polystyrene-conjugated diene random copolymer as well as preparation method and application thereof

    CN113563514A

  • Oil-extended hydrogenated diblock copolymer

    US4102849A